Peran Inovation Relation Behavior dalam Memperkuat Hubungan Psychological Empowerment dan Affective Commitment Employee pada Customer Satisfaction - Sahara Sahara (JBIMA (Jurnal Bisnis dan Manajemen), 2016)
The purpose of this paper is to seek to examine the mediating role Relation Innovation Behavior (IRB) in association with psychological empowerment (PE) and Affectif Commitment employe (AC) to improve Customer Satisfaction (CS) in the industry small and medium enterprises (SME) sector services in Cirebon, Indonesia. Respondents in this study were employees and managers of SMEs by 115 respondents. Structural equation modeling and confirmatory factor analysis was performed to evaluate hypothetical model. The size of the reliability and validity were also examined. Findings: Statistical analysis showed that following each PE and AC have a positive impact on the AC, and AC affecting CS. The practical implications of this research provide a complete picture of power relations in building relationships in the SME sector and offer a deeper understanding of the factors affecting the AC, and how air conditioning affects CS. This understanding will help practitioners formulate human resources policies are effective and restructure their training programs to increase the level of commitment and performance of their employees who directly be felt customers in improving customer satisfaction.